Genetic Identification of Critically Endangered Orangutans in Captivity - Siti Norsyuhada, Kamaluddin; Salmah, Yaakob; Wan Mohd Razi, Idris; Sabapathy, Dharmalingam; Jeffrine Japning, Rovie-Ryan; Badrul Munir, Md Zain (Penerbit UMT, 2018)
A large numerals of the orangutans’ genetic status in captivity is unknown to its exact, thus complicates the translocation process to their true natural habitat. A study was carried out to identify 37 captive orangutans in Peninsular Malaysia at the species and subspecies level using mitochondrial DNA (mtDNA) displacement loop (D-loop) region DNA sequences. Orangutan genetic samples were provided by the Bukit Merah Orang Utan Island (BMOUI), Zoo Negara, Zoo Taiping and the A’ Famosa. Total genomic DNA was extracted from both fecal and blood samples. Polymerase chain reaction (PCR) was performed using specific primers for the orang utan. Data analyses were carried out using distance and character based approaches, namely the neighbor joining (NJ), maximum parsimony (MP), and Bayesian techniques. About 8 individuals were identified as Pongo pygmaeus pygmaeus, 20 as P. p. morio, 5 as P. p. wurmbii, and 4 as P. abelii. All samples were successfully identified with high probabilities. The results obtained in this study contributes to improve the understanding of captive orangutans’ genetic identification, and indirectly, a guide to the authorities in developing plans for the management in captivity and conservation of primates in Malaysia using molecular data